Peran Customer Service dalam Meningkatkan Kualitas Pelayanan Nasabah PT. Bank Rakyat Indonesia (Persero) TBK Kantor Cabang Madiun - Nur Okluanty, Fibi; Imaningsih, Niniek; Fadil, Cholid (Al-Kharaj: Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2024)
Achieving customer happiness necessitates the adoption of enhanced cutomer service. The present study examines how cutomer service might enhance cutomer servi satisfaction at the Madiun Branch Office of PT Bank Rakyat Indoensia (Persero)Tbk. For the intention of understanding how customer service contributes to the PT Bank Rakyat Indoensia (Persero)Tbk Madiun Branch Office’s improved customer service. Qualitative research with data gathering methods from libraries is the sort of study that’s is being done. The study’s findings show that PT Bank Rakyat Indoensia (Persero)Tbk Madiun Branch Officeis customer service is crusial to the provision of services to clients